Patterns of Pediatric Ear, Nose and Throat Disorders in a Tertiary Care Hospital of Western Nepal: A Cross-Sectional Study - Regmi, Shiva; Chaudhary, Nagendra; Shrestha, Sandeep; Pathak, Santosh`; Gupta, Badri Kumar; Swar, Ravi; Kurmi, Om Prakash (Journal of Universal College of Medical Sciences, 2019)
INTRODUCTION: In outpatient department (OPD) of hospital in low and middle income countries (LMICs), pediatric ear, nose and throat (ENT) disorders are common and huge variation in number is being reported in different seasons. This study aimed to study the prevalence and seasonal effect of ENT disorder in children. MATERIAL AND METHODS: One year (Jan-Dec, 2015) retrospective data of children (0 months-17 years) visiting ENT outpatient (ENT-OPD) department at Universal College of Medical Sciences-Teaching Hospital, Nepal was analysed. Descriptive statistics were calculated to report the prevalence of ENT disorders for various sub-groups including season. In addition to quantifying the prevalence of ENT disorders in children, the seasonal influence of each disorder was analysed. RESULTS: Out of 14,126 patients visiting the ENT-OPD, 3,423 (24.23%) were children. The mean age of children having ENT- disorders were 8.4±5.1, 10.6±4.6 and 10.7±4.7 years respectively with male-female ratio of 1.3:1. During all seasons 2,645 (77.3%) had ear problems, 328 (9.6%) nose disorders and 450 (13.14%) throat disorders. The percentage of children with ear disorders declined significantly with increase in age unlike those with nose and throat disorders (P < 0.001). Seasonal trend analysis showed that children had significantly higher number of ear disorders during summer and autumn seasons (P <0.001) whereas nose disorders were more common in spring and winter seasons (P<0.001) with chronic otitis media and wax being the main types of ear disorders and deviated nasal septum (DNS) for nose disorders. Among the throat disorders, tonsillitis was most prevalent in all seasons followed by pharyngitis. CONCLUSION:- The study suggests a clear seasonal trend in the prevalence of ENT disorders that can be used for advanced planning and management of the conditions in hospitals.